2016
DOI: 10.15414/jmbfs.2016.5.4.301-305
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Contamination and Mycotoxin Production by Aspergillus Spp. In Nuts and Sesame Seeds

Abstract: This work reports the occurrence of the fungal flora and evaluates the mycotoxigenic potential of Aspergillus genera in 63 samples of oil seeds and nuts (almonds, pistachio and sesame seeds). Fungal isolation and identification revealed the presence of 5 genera (Aspergillus, Penicillium, Cladosporium, Mucor and yeasts) with the predominance of Aspergillus section Nigri. A number of 138 strains of Aspergillus section Nigri and 91 of Aspergillus section Flavi were isolated and tested for their ability to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
2
8
1
Order By: Relevance
“…These results are matched with previous studies that isolate and diagnose some fungi from nuts which offered for human usages such as Rhizopus spp, A .niger, Penicillium spp, Rhizoctonia spp, Chaetomium spp, Trichoderma spp and Fusarium spp (AL-Rawi , 2009). Our results are in good agreement with the study results of Mimoune (2016) who showed that Aspergillus sp. and Penicillium sp.…”
Section: Results and Discussion Detection And Isolation Of Pathogenicsupporting
confidence: 93%
“…These results are matched with previous studies that isolate and diagnose some fungi from nuts which offered for human usages such as Rhizopus spp, A .niger, Penicillium spp, Rhizoctonia spp, Chaetomium spp, Trichoderma spp and Fusarium spp (AL-Rawi , 2009). Our results are in good agreement with the study results of Mimoune (2016) who showed that Aspergillus sp. and Penicillium sp.…”
Section: Results and Discussion Detection And Isolation Of Pathogenicsupporting
confidence: 93%
“…In this study, chemotypes II (produce more AFB2 than AFB1), chemotype III (producers of AFB but not CPA) and chemotype VI (producers of AFB, AFG, and CPA) were not found. The same results were reported in Algeria by Ait Mimoune et al () and Riba et al (). The incidence of non‐aflatoxigenic isolates representing chemotype V that was found in our study is relatively low (6.4%) in comparison with results reported by other authors (Razzaghi‐Abyaneh et al, ; Rodrigues et al, ; Sánchez‐Hervás, Gil, Bisbal, Ramón, & Martínez‐Culebras, ; Vaamonde et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Based on this identification, A. flavus strains were the predominant (78.5%), followed by 19.2% of A. tamarii , 1.7% of A. parasiticus , and 0.6% of A. alliaceus . The dominance of A. flavus have been reported in other commodities from Algeria such as wheat and wheat products (Riba et al, ), dried fruits (Ait Mimoune et al, ), peanuts (Guezlane‐Tebibel et al, ), and spices (Azzoune et al, ). Similar results were shown in other African countries like Tunisia for cereals (Jedidi et al, ; Jedidi, Cruz, González‐Jaén, & Said, ), and Tunisian vineyards (Melki Ben Fredj et al, ), Morocco for wheat grains (Hajjaji et al, ) and Nigeria for maize and marketed poultry feed (Atehnkeng et al, ; Ezekiel, Atehnkeng, Odebode, & Bandyopadhyay, ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations